Effect of various processing parameters on the quality of papaya fruit tea - Muhammad, Ida Idayu; Abdul Majid, Fadzilah Adibah; Md. Zaki, Nurul Asyikin (Universiti Teknologi Malaysia, 2005)
Exotic fruits from which drinks are ma de in most tropical countries are so abundant and such in a great variety, that it would probably be impossible for people to sample all of them, but they worth a try. Some of the great varieties of fruits used in drinks are bananas, guavas, papayas, oranges, pineapples, grapes, mangoes, watermelon, coconuts, longans, rambutans, strawberries, lime and tamarind.